Environmental and behavioral factors associated with household transmission of SARS-CoV-2 in children and adolescents - Faétila dos Santos Oliveira; Rafael Alves Guimarães; Rafael Alves Guimarães; Eliane Terezinha Afonso; Lusmaia Damaceno Camargo Costa; Karina Machado Siqueira; Solomar Martins Marques; Claci Fátima Weirich Rosso; Paulo Sérgio Sucasas da Costa; Alessandra Vitorino Naghettini; Maria Alves Barbosa; Maria Alves Barbosa; et al. (Frontiers Media S.A., 2023)
ObjectiveTo analyze the association between risk behaviors and environmental factors and SARS-CoV-2 infection in children and adolescents in the family environment.MethodsCross-sectional study. A total of 267 children and adolescents aged 5-19 years who have contact with COVID-19-positive essential workers were tested between June and October 2020. Behavioral and environmental variables associated with SARS-CoV-2 infection were investigated. Association between these variables was performed using Poisson regression.ResultsSARS-CoV-2 prevalence was 25.1%. Following the confirmation of COVID-19 diagnosis of the index case, 92.1% of adults reported hand hygiene and 83.5% showed habits of respiratory etiquette. However, 12.7% wore masks in common areas of the residence before COVID-19. Sharing common objects was a risk factor for SARS-CoV-2 infection in the sample.ConclusionSharing objects among family members was identified as a risk factor associated with SARS-CoV-2 infection in children and adolescents who lived with infected adults. There was high frequency of hand hygiene and low prevalence of mask use.